2018
DOI: 10.2147/cmar.s162168
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implications of circulating Epstein–Barr virus DNA for extranodal natural killer/T-cell lymphoma, nasal type: a meta-analysis

Abstract: IntroductionTo evaluate the prognostic value of circulating Epstein-Barr virus DNA for extra-nodal natural killer/T-Cell lymphoma, nasal type (ENKTL), we performed a meta-analysis of published studies that provided survival information with pre-/post-treatment circulating EBV DNA.MethodsEligible studies that discussed prognostic significance of circulating EBV DNA in ENKTL were included. Random effects models were applied to obtain the estimated hazard ratios and 95% confidence intervals to evaluate prognostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Previous studies mainly focused on the involvement and prognostic value of non-immune factors in ENKTL, such as EBV DNA 31. More recently, several studies investigated the prognostic value of ALC in T-cell NHL.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies mainly focused on the involvement and prognostic value of non-immune factors in ENKTL, such as EBV DNA 31. More recently, several studies investigated the prognostic value of ALC in T-cell NHL.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative polymerase chain reaction for EBV DNA might not be available in all hospitals. In addition, the reference values, measuring procedure and sample type (whole blood or plasma) [ 21 ], and the definition of high titer is not yet standardized [ 22 ]. Because of these limitations, the PINK-E model incorporates a detectable EBV-DNA titer regardless of the sample type.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been reported that detection of circulating EBV-DNA at the end of the treatment was associated with a high relapse rate. 37 Therefore, serum EBV-DNA has been added to the risk stratification of ENKTL, and patients with high copy number of serum EBV-DNA were treated with more intensive chemotherapy. 38,39 EBV-DNA in peripheral blood can be used as a marker for the precise diagnosis and treatment, outcome evaluation, and prognosis prediction of ENKTL.…”
Section: Discussionmentioning
confidence: 99%